The Significance of Listening to Street Children: A Qualitative Case Study - Gabriel Julien (New Ideas Concerning Arts and Social Studies Vol. 3, 2025)
Globally, street children are seldom viewed positively, and they habitually encounter prejudice and discrimination daily. They are constantly disregarded, and very few people listen to them. It is instructive to note that they are normal human beings and have a right to express themselves. Hence, this research was conducted among seventeen street children at Rose Institution, a drop-in centre, in Trinidad and Tobago. The principal objective of this qualitative case study provide these children with an opportunity to express their views and opinions. Although they live in Rose Institution, they continue to frequent the streets. Published research indicates that there exists a lack of information about their lives and experiences, and this research fills that gap. Semi-structured interviews and open-ended questionnaires were employed, and data were triangulated. Data revealed that listening is necessary to try to understand the lives, goals and aspirations of these children. Listening can also diminish the barrier between these children and mainstream society. Although it is difficult and demanding, it is strongly suggested that professionals, policy makers and indeed all citizens listen carefully to the voices of these children to bring about some meaningful change.